Non-universal critical properties of a symmetrical binary fluid mixture - Patsahan, O.V.; Melnyk, R.S.; Kozlovskii, M.P. (Condensed Matter Physics, 2001)
We study non-universal critical properties of a symmetrical mixture using
the recently proposed approach and the method of layer-by-layer integration
of a partition function. Both the gas-liquid critical point properties (temperature
and density) and the fluid-fluid demixing temperature of a symmetrical
hard-sphere square-well mixture are calculated depending on its
microscopic parameters: the parameter r measuring the strength of interactions
between the particles of dissimilar and similar species and the
parameter λ measuring the width of the potential well. Ми вивчаємо неуніверсальні критичні властивості симетричної бінарної суміші, використовуючи недавно запропонований підхід і метод пошарового інтегрування статистичної суми. Для симетричної
суміші твердих сфер, які взаємодіють з потенціалом прямокутної
ями, обчислені властивості критичної точки газ-рідина (температура
і густина) і температура незмішування флюїд-флюїд залежно від мікроскопічних параметрів: параметра r , який вимірює силу взаємодії
між частинками неподібних і подібних сортів, і параметра λ , який вимірює ширину потенціальної ями.